2016
DOI: 10.4172/2167-7921.1000225
|View full text |Cite
|
Sign up to set email alerts
|

Non-surgical and Non-pharmacological Treatment of Knee Pain

Abstract: Knee pain is an increasingly common presentation to general practitioners both in the United Kingdom and worldwide and is thought to be caused by a combination of the obesity epidemic, the ageing population and continuing worldwide population growth. Two distinct aetiologies of knee pain have been described: a bony-type which is usually degenerative in nature; and a ligamentous-type which usually occurs as a result of acute injury but then predisposes to the development of bony-type in later life. There are a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Many studies have suggested that NPIs have a potential to alleviate the symptoms especially pain. 10 This is the first line of therapy in hospitals. But obtaining a favourable impact of NPIs depends on combination of many factors.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have suggested that NPIs have a potential to alleviate the symptoms especially pain. 10 This is the first line of therapy in hospitals. But obtaining a favourable impact of NPIs depends on combination of many factors.…”
Section: Discussionmentioning
confidence: 99%
“…This is still significant and clinicians should encourage overweight patients with knee OA to lose weight regardless of many other health benefits such as cardiovascular disease, diabetes, etc. Atukorala et al, also demonstrated dose-dependence between weight loss and a reduction in knee pain and symptoms during an 18-week program, indicating this is an important and valid lifestyle intervention to treat knee pain 32 .…”
Section: Goals Of Treatmentmentioning
confidence: 95%
“…The first neuromuscular exercise program developed for use in patients with OA was published in 2010 29 . A recent Cochrane review identified 32 trials investigating a variety of land-based therapeutic exercise programs. Results of a meta-analysis showed mean treatment benefits for both knee pain and physical function.…”
Section: Goals Of Treatmentmentioning
confidence: 99%
“…Physical therapies, bracing and lifestyle management are among many of the physical options available [8]. Oral pharmacological strategies such as simple analgesia, non-steroidal anti-inflammatory drugs (NSAIDs), corticosteroids (CS) and dietary supplements such as glucosamine are all routinely used in an attempt to control pain [9].…”
Section: Introductionmentioning
confidence: 99%